Bilesional serpiginous cutaneous ectoparasitosis in a Greek grazier. (2019) - Dimitriadis, I
Abstract: A Balkan case of paucilesional truncal autochthonous hookworm-related cutaneous larva migrans contracted during winter in a cowman, successfully treated by 10% albendazole topical preparation.